TRIP12 promotes small-molecule-induced degradation through K29/K48-branched ubiquitin chains - Kaiho-Soma, Ai; Akizuki, Yoshino; Igarashi, Katsuhide; Endo, Akinori; Shoda, Takuji; Kawase, Yasuko; Demizu, Yosuke; Naito, Mikihiko; Saeki, Yasushi; Tanaka, Keiji; Ohtake, Fumiaki (Molecular cell, 2021)
Targeted protein degradation is an emerging therapeutic paradigm. Small-molecule degraders such as proteolysis-targeting chimeras (PROTACs) induce the degradation of neo-substrates by hijacking E3 ubiquitin ligases. Although ubiquitylation of endogenous substrates has been extensively studied, the mechanism underlying forced degradation of neo-substrates is less well understood. We found that the ubiquitin ligase TRIP12 promotes PROTAC-induced and CRL2VHL-mediated degradation of BRD4 but is dispensable for the degradation of the endogenous CRL2VHL substrate HIF-1α. TRIP12 associates with BRD4 via CRL2VHL and specifically assembles K29-linked ubiquitin chains, facilitating the formation of K29/K48-branched ubiquitin chains and accelerating the assembly of K48 linkage by CRL2VHL. Consequently, TRIP12 promotes the PROTAC-induced apoptotic response. TRIP12 also supports the efficiency of other degraders that target CRABP2 or TRIM24 or recruit CRBN. These observations define TRIP12 and K29/K48-branched ubiquitin chains as accelerators of PROTAC-directed targeted protein degradation, revealing a cooperative mechanism of branched ubiquitin chain assembly unique to the degradation of neo-substrates. [Display omitted] •TRIP12 facilitates PROTAC-induced and CRL2VHL-mediated degradation of BRD4•TRIP12 specifically assembles K29-linked Ub chains•TRIP12 and CRL2VHL cooperatively assemble K29/K48-branched Ub chains on BRD4•Targeted degradation uses unique mechanisms rather than a simple “hijack” Targeted protein degradation is an emerging therapeutic paradigm. Kaiho-Soma et al. found that the K29-linkage specific ubiquitin ligase TRIP12 promotes small-molecule-induced and CRL2-mediated degradation of neo-substrates such as BRD4. They identified K29/K48-branched ubiquitin chains as a ubiquitin code used for chemically induced targeted protein degradation.